Estresse e estratégias de enfrentamento/coping em mulheres com câncer de mama - Alves, Pricilla Cândido (2010)
The various changes in the daily of women that have breast cancer, arising of cognitive changes, may represents threat to your manteinance biopsychosocial, being a stressful factor because request coping strategies whose aim is the reduction, elimination or management of stress. Thus, the study aimed to verify the occurrence of stress and the use of coping strategies in the daily of women diagnosed of breast cancer. It is a cross-sectional study, descriptive-exploratory, realized in the MEAC’s Mastology ambulatory and in the CRIO’s Chemotherapy sector. The population were composed by women that had been diagnosed recent with breast cancer and were in treatment in the locals refered. With criteria established and using the sampling procedure by convenience were included 21 women in the study and that were in the locals of collected during the months from April to July 2010. Used like instrument to obtain the dates a structured interview guide with sociodemographic dates and disease history, the Inventory of Symptoms of Stress to Adults of Lipp (ISSL) and the Ways of Coping Scale (WCS). The dates were stored and analysed in the SPSS program version 17.0, calculating mean and standard deviation to continuous variable, frequency percentage to categorically and the tests 2 and ANOVA in the verification of association among variables. All the analyses a p value<0.05 was considered statistically significant. The mean of age was 57,76 (DP=13,2), the instruction level was low average four to six years, the family income had a mean of R$966,00 (DP=0,4) and observed the mean of two children by women. Most of women (85,7%) had breast cancer with surgical indication like treatment, having most indication to realize total mastectomy (42,9%). From the total women, 42,8% had indication to realize neoadjuvant chemotherapy like complementary therapy. The stress diagnostic were present in 66,7% of sample while in 33,3% of patients it was not observed. From patients that were with stress, the mean phases were alarm (33,3%) and resistance (33,3%). In the group with stress, the mean type of coping used was the search for religious practice (42,8%) and in the group without stress observed the focus on the problem in the most of women (23,7%), having association statistically significant between these variables (test 2 ; p=0,007). The means of ages, income and number of children among women and the relation with the type of coping not demonstred association statistically significant with the test F of Snedecor (ANOVA). The research demonstred that the women with breast cancer were significantly stressed and used like way of coping the religious practice, having not occurrence of stress among women that were looking to face the disease of a resolving way. Anyway the stress situations caused by breast cancer request a response of women, be a more adaptive response or not, thus, the woman need to find the possible mechanism to be used in the coping process. It is believed that in this aspect the nursing have an important role to realize in order to mediate the more adapter responses in the disease’s situation.